Out‐of‐the‐Box Nanocapsules Packed with On‐Demand Hydrophobic Anticancer Drugs for Lung Targeting, Esterase Triggering, and Synergy Therapy. Issue 8 (12th January 2021) - Zhao, Di; Jiang, Kai; Wang, Yuqi; Cheng, Jin; Mo, Fangli; Luo, Tao; Guo, Yuanyuan; Zhang, Chuan; Song, Jie
Abstract: Most anticancer drugs, particularly paclitaxel (PTX), are suffering the challenges of cancer chemotherapy due to their poor water‐solubility, high toxicity under effective therapeutic dosages, and multi‐drug resistance. Currently, nanoscale drug delivery systems (DDSs) represent an efficient platform to overcome the above challenges. However, those DDSs generally need a careful design of conjugation, complexation, or co‐self‐assembly. Herein, a facile out‐of‐the‐box nanocapsule is developed not only to be easily packed with on‐demand hydrophobic anticancer drugs (up to 76% of loading efficiency for PTX), but also to be loaded with other concomitant drugs for synergy therapy (Itraconazole (ITA) here as P‐glycoprotein inhibitor for drug resistance and antiangiogenic agent for combination therapy with PTX). Three kinds of biocompatible poly(ethylene glycol) dimethacrylates (PEGDM) derivatives usually as cross‐linking agents are selected and successfully constructed adequate nanocapsules with single monomer as shell materials. More importantly, as‐prepared nanocapsules have abilities of esterase triggering and lung targeting. Both in vitro and in vivo studies showed that the drug‐loaded nanocapsules can effectively inhibit tumor growth and vascular proliferation in PTX‐resistant tumor models without apparent systemic toxicity. The above results demonstrate that the nanocapsule system provides an effective and universal strategy for lung targeting, esterase triggering, and synergy therapy. Abstract : A facile out‐of‐the‐box nanocapsule is developed not only to be easily packed with on‐demand hydrophobic anticancer drugs (up to 76% of loading efficiency for paclitaxel (PTX)), but also to be loaded with other concomitant drugs for synergy therapy (Itraconazole here as P‐glycoprotein inhibitor for drug resistance and antiangiogenic agent for combination therapy with PTX).